The competence of a coach in sports: How does it correlate with athlete motivation? - Immanuel Mu'ammal; Abdurrohman Muzakki; Erie Awalil Fakhri; Edi Setiawan (UIR Press, 2022)
Sports coaches hold integral roles in sports organizations. As important figures for athletes, coaches are responsible for maintaining athletes’ motivation which will drive their performances in matches. To motivate athletes, coaches must possess good competence which reflect their quality as coaches. This study analyzes the effect of coach competency on athlete motivation. Coach competency in this study is represented by four indicators: motivation competency, game-strategy competency, technique competency, and character-building competency. Each and every indicator’s effect on athlete motivation was investigated. The instrument in this study used a questionnaire with 42 question items. This study is an explanatory research conducted on 114 student basketball athletes in Indonesia as respondents. Data analysis was conducted using SEM-PLS on the WARP-PLS 7 software. The results of this research show that overall, motivation competency, technique competency, character building competency, and game-strategy competency which represents the coach competency variable have a positive effect on athlete motivation (p<0.05), while motivation competency has no effect on athlete motivation (p>0.05). Game strategy competency, technique competency, and character building competency has positive effects on athlete motivation (p<0.05). This research contributes to increasing scientific knowledge among coaches and athletes about the importance of competence for the motivational aspect. The limitation in this study is that the sample used only comes from basketball athletes so it is not yet known whether there is a similar relationship between the competence and motivation of other sports coaches. Therefore, future research can examine the relationship between the competence and motivation of coaches in sports such as football, volleyball, and handball.